2021
DOI: 10.3390/cells10092429
|View full text |Cite
|
Sign up to set email alerts
|

Brain Immune Interactions—Novel Emerging Options to Treat Acute Ischemic Brain Injury

Abstract: Ischemic stroke is still among the leading causes of mortality and morbidity worldwide. Despite intensive advancements in medical sciences, the clinical options to treat ischemic stroke are limited to thrombectomy and thrombolysis using tissue plasminogen activator within a narrow time window after stroke. Current state of the art knowledge reveals the critical role of local and systemic inflammation after stroke that can be triggered by interactions taking place at the brain and immune system interface. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 157 publications
(207 reference statements)
1
14
1
Order By: Relevance
“…The role of inflammation in IS has drawn great attention since neuronal death caused by occlusion of cerebral blood flow can trigger both local and systemic immune responses ( 35 , 36 ). Accordingly, individuals with signs of inflammation or corresponding biomarkers have an increased risk of stroke ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of inflammation in IS has drawn great attention since neuronal death caused by occlusion of cerebral blood flow can trigger both local and systemic immune responses ( 35 , 36 ). Accordingly, individuals with signs of inflammation or corresponding biomarkers have an increased risk of stroke ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Once the intestinal mucosa is damaged, the number and structure of the intestinal flora will change immediately. Previous studies found that the gut microbiota changed significantly through the brain-gut axis after ICH [38] (Table 2). After stroke, activated microglia and injured brain tissue release DAMPs and cytokines, leading to endothelial cell activation and the expression of chemokines and adhesion molecules, which further promote the recruitment of immune and inflammatory cells from the bloodstream to the damaged site in the brain [39].…”
Section: Gut Microbiota Dysbiosis Is Induced After Ichmentioning
confidence: 90%
“…DAMPs can promote the interaction between APCs and receptors to activate adaptive immune responses, which are mediated by effector T cells ( 47 ). Effector T cells play a role in the adaptive immune response by recruiting to ischemic areas, traversing the injured BBB, releasing inflammatory cytokines such as interferon gamma (IFN-γ) in the brain parenchyma, and ultimately leading to delayed neurotoxicity ( 39 , 48 ). The immune response after IS is a self-limiting pathophysiological process that gradually subsides under the combined action of regulatory T cells and B cells, preparing for the structural and functional reconstruction of the later brain injury site.…”
Section: Pathological Mechanisms Of Immune Inflammation In Ismentioning
confidence: 99%